Intraoperative monitoring of visual evoked potentials in neurosurgery of sellar region tumors’ removal - S. A. Anikin; V. Ye. Olyushin; T. N. Fadeyeva; A. Yu. Ulitin (Бюллетень сибирской медицины, 2008)
Visual functions in the postsurgical period are among the most important factors determining the quality of life in patients with tumors of sellar region. Advances in surgical treatment of patients with sellar tumors require exact evaluation of degree the optic nerves and chiasm being involved in the pathological process. The problem of approapriate surgical treatment cannot be solved without its consideration in the neuroophthlmological aspect. The main purpose of intra-operative monitoring of visual evoked potentials is well-timed revealing and prevention of damage of the visual system.